2022
DOI: 10.1111/j.1755-3768.2022.056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ocular surface disease symptoms and patient satisfaction in dry eye disease after 84 days of treatment with preservative‐free eye drops containing sodium hyaluronate and trehalose

Abstract: PurposeDry eye disease (DED) has a multifactorial etiology, including insufficient tear production and/or excessive tear evaporation linked to multiple conditions. A preservative‐free eye drop formulation containing sodium hyaluronate and trehalose (SH‐THL, Thealoz® Duo) capitalizes on the bioprotectant properties of trehalose. This study evaluated the improvement of ocular surface disease (OSD), dry eye signs and symptoms, treatment satisfaction in patients with DED receiving SH‐THL.MethodsMulti‐center, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another study done by Mateo-Otobia et al . [ 17 ] also showed that preservative-free eye drop formulation containing sodium hyaluronate and trehalose has a better OSDI score compared to eye drops containing preservatives. The mean OSDI score at baseline was in the range of mildly affected quality of life and the mean score at follow-up was in the range of normal QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Another study done by Mateo-Otobia et al . [ 17 ] also showed that preservative-free eye drop formulation containing sodium hyaluronate and trehalose has a better OSDI score compared to eye drops containing preservatives. The mean OSDI score at baseline was in the range of mildly affected quality of life and the mean score at follow-up was in the range of normal QoL.…”
Section: Discussionmentioning
confidence: 99%